Using Laboratory Brand Preference Scales to Predict Consumer Brand Purchases - Pessemier, Edgar; Burger, Philip; Teach, Richard; Tigert, Douglas (Management Science, 1971)
Laboratory measures of brand preferences and survey measures of demographic, media exposure, attitudinal, activity and opinion characteristics of individual consumers have been combined to predict brand purchases in the market. Brands in the tooth paste, liquid household cleaner and cake mix product categories were employed in a set of laboratory experiments. Preference scales derived from the experiments are used in three separate models to predict the subject's purchases recorded in seven months of diary data. The behavioral implications and predictive power of the models are interesting from both theoretical and applied points of view.